A compact, high-density gamma-detection module for Time-of-Flight measurements in PET applications - Sacco, Ilaria; Dohle, R.; Fischer, Peter; Piemonte, C.; Ritzert, Michael (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
We present a very compact γ-detection module primarily designed for PET applications. On a total area of about 30×30mm2, 144 SiPM photodetectors coupled to scintillator crystals are read out individually with fast timing ASICs. The core of the module is a LTCC ceramic substrate with internal water channels for efficient and stable liquid cooling. The top side of the LTCC is covered by 12×12 SiPMs in a regular pitch of 2.5mm. The SiPMs are designed in the RGB-HD technology from FBK with a single cell size of 25×25μm2, very low dark-count rate and stable performance over a wide temperature range from 0 to 20°C. The readout of the SiPMs is done with 4 specialized PETA5 ASICs flip-chip mounted to the bottom side of the substrate. Each chip has 36 readout channels (available in single or differential ended configuration) with self-triggered hit detection, a very low noise discriminator, signal amplitude integration and digitization, a TDC with 50ps binwidth, neighbor logic and fast veto mechanisms. The full height of the assembly, including the connector to the main readout board, is less than 1cm. In a 1:1 coupling configuration with 10mm high LYSO scintillator arrays for detection of 511keV gammas, the module has already reached 205ps CRT time resolution (FWHM in coincidence between channels on two different modules), sufficient for ToF operation in PET. The module design, details on chip operation and latest results with LYSO arrays are described.